Calidad del agua y su influencia en la eficacia de productos pesticidas - Villacís Galarza, Erick Iván (2024)
Worldwide, water is of utmost importance for plants, the deterioration of its quality is due to the discharge of various liquids by the constant use by farmers in Ecuador in order to preserve the quality of the crop, for agricultural use we must know the quality of water by evaluating the physicochemical parameters such as pH, alkalinity, turbidity, conductivity, temperature help determine their suitability for use in the field, even more important to determine the effectiveness of a pesticide, the dissolution mechanism of pesticides consists of the molecules that make up the active ingredient of the same, reducing their size until they are completely diluted through a process called hydrolysis, pH, alkalinity and turbidity are the main parameters that directly influence the effectiveness of pesticides, This is due to the fact that in the case of pH reduces the useful life of the mixture, while alkalinity causes the hydroxyls to significantly degenerate the effectiveness of the active ingredient of the pesticide, and turbidity in the water causes the suspended particles to bind with the pesticide itself, for this reason, it is recommended to analyze the water prior to the cultivation of the crop in the chosen area, to know how the pesticide dissolution mechanism works and to use coadjuvants, pH regulators and other tools that help to increase the effectiveness of the product when the water does not meet the required standards.